Resposta :
Resposta:
. x³ - 7x + 6
Explicação passo a passo:
.
. Multiplicação de polinômios
.
. (x - 1).(x - 2).(x + 3) = (x² - 2x - x + 2).(x + 3)
. = (x² - 3x + 2).(x + 3)
. = x^3 + 3x² - 3x² - 9x + 2x + 6
. = x^3 - 7x + 6
.
(Espero ter colaborado)
Resposta:
[tex]\sf{segue \: abaixo \: a \: resposta}[/tex]
Explicação passo-a-passo:
[tex]\sf{(x-1) (x-2) (x+3)}[/tex]
[tex]\sf{( {x}^{2} - 2x - x + 2)x(x + 3)}[/tex]
[tex]\sf{( {x}^{2} - 3x + 2)x(x + 3)}[/tex]
[tex]\sf{ {x}^{3} + 3 {x}^{2} - {3x}^{2} - 9x + 2x + 6 }[/tex]
[tex]\sf{ + {3x}^{2} - {3x}^{2} = 0}[/tex]
[tex]\sf{ {x}^{3} - 9x + 2x + 6}[/tex]
[tex]\boxed{\boxed{{\sf{\boxed{\boxed{{\sf{ {x}^{3} - 7x + 6}}}}}}}}[/tex]